Determinan Akuntabilitas Pengelolaan Keuangan Organisasi Nonlaba - Evi Yuanita; Bambang Suripto (Universitas Muhammadiyah Malang, 2022)
The mainly funding source of NGOs come from community donations that highly dependent on the high level of accountability. However, several recent surveys show that public trust in NGOs is the lowest compared to other institutions. This shows that the accountability of NGO still needs to be improved. Based on legitimacy and stewardship theory, this study analyzes the impact of internal control systems, transparency, with restrictions fund, presentation and accessibility of financial statements on NGOs accountability of financial management. Sample of the research consisted of 97 NGOs with 120 respondents and used purposive sampling method. To collect data, a questionnaire was used which was distributed to staff and finance managers of NGOs. The results of study provide evidence that internal control systems, transparency and with restrictions fund have a positive effect, presentation of financial statements has no effect and accessibility has a negative effect on the accountability of NGO financial management. Result of this study can be used as input for efforts to increase the accountability of NGO financial management. This study also emphasizes some implications for improving accountability of NGO financial management.